2008
DOI: 10.1016/j.anbehav.2008.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity with breeding habitat improves daily survival in colonial cliff swallows

Abstract: One probable cost of dispersing to a new breeding habitat is unfamiliarity with local conditions such as the whereabouts of food or the habits of local predators, and consequently immigrants may have lower probabilities of survival than more experienced residents. Within a breeding season, estimated daily survival probabilities of cliff swallows (Petrochelidon pyrrhonota) at colonies in southwestern Nebraska were highest for birds that had always nested at the same site, followed by those for birds that had ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 63 publications
0
65
0
Order By: Relevance
“…The analyses reported here and elsewhere (Brown and Brown 1996, 2000a, Brown et al 2000, 2008, Roche et al 2011 reveal that the extensive colony size variation in Cliff Swallows is likely generated by evolutionary (EVO), ecological (ECO), and behavioral (BEH) processes working in complex and sometimes synergistic ways. Cliff Swallows may choose sites and colony sizes based in part on (1) heritable tendencies toward small or large groups that have been selected for by (2) expected phenotypic-dependent payoffs in different group sizes (EVO), while at the same time individuals likely refine colony selection by (3) familiarity with particular sites (ECO) and (4) prior assessment of the probability of success at a colony site or by aggregating with conspecifics already settled (BEH).…”
Section: Discussionmentioning
confidence: 99%
“…The analyses reported here and elsewhere (Brown and Brown 1996, 2000a, Brown et al 2000, 2008, Roche et al 2011 reveal that the extensive colony size variation in Cliff Swallows is likely generated by evolutionary (EVO), ecological (ECO), and behavioral (BEH) processes working in complex and sometimes synergistic ways. Cliff Swallows may choose sites and colony sizes based in part on (1) heritable tendencies toward small or large groups that have been selected for by (2) expected phenotypic-dependent payoffs in different group sizes (EVO), while at the same time individuals likely refine colony selection by (3) familiarity with particular sites (ECO) and (4) prior assessment of the probability of success at a colony site or by aggregating with conspecifics already settled (BEH).…”
Section: Discussionmentioning
confidence: 99%
“…A corollary prediction is that a decline in breeder residual reproductive value, through increased mortality and/or decreased fecundity, should favour the choice of concealed nests, increasing the survival prospects of current oVspring (Öst et al 2008a) at the potential expense of adult life span. Alternatively, familiarity with local predator hunting strategies (Brown et al 2008), ability to assess predation risk (Pöysä and Pesonen 2007) or to escape predation, may contribute to age-related improvement in selecting nest sites (Pärt 1995). Experienced breeders may be able to select concealed nests at no apparent cost to their life expectancy, provided that they are capable of, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Even though a recent study showed that increasing dispersal activity decreased daily survival of a small-sized passerine (Brown et al 2008), the situation could be different in long-lived species such as eiders, in which long-term survival is more important for life-time reproductive success than the current season's breeding success. For example, it is possible to envision a situation in which failed nesters re-using the same nesting site would be more likely to be killed by predators, and will thus be absent from our current data.…”
Section: Consequences Of Breeding Dispersalmentioning
confidence: 90%
“…By returning, individuals may use previous experience of the breeding site to maintain or improve breeding success, while leaving may decrease survival or reproductive success, e.g. by delaying mate acquisition or nest finding and establishment (Wiggett and Boag 1993;Blums et al 2003;Brown et al 2008;Robbins et al 2009). On the other hand, selecting a new location for breeding may be beneficial if a better site than the original one can be found (Clobert et al 2001).…”
Section: Introductionmentioning
confidence: 99%